The Impact of Environmental Uncertainty and Sense of Urgency on Individual Innovation in Bali's Renewable Energy Startups - Suryandari, Ratnawati Yuni; Muhtadi, Muhamad Ammar; Pahrijal, Rival (Westscience Press, 2025)
This study investigates the impact of environmental uncertainty and sense of urgency on individual innovation in renewable energy startups in Bali. In dynamic and resource-constrained startup environments, the ability to innovate is critical for survival and competitiveness. A quantitative approach was employed, surveying 130 respondents from various renewable energy startups using a Likert-scale questionnaire. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to test hypothesized relationships. The results indicate that both environmental uncertainty (β = 0.342, p < 0.001) and sense of urgency (β = 0.540, p < 0.001) significantly influence individual innovation. Furthermore, sense of urgency partially mediates the effect of environmental uncertainty on innovation, highlighting its role as a psychological catalyst that translates external pressures into actionable innovative behaviors. The findings provide theoretical contributions by integrating contingency theory and self-determination theory, and offer practical implications for startup managers and policymakers seeking to foster innovation in uncertain renewable energy markets.